2001
DOI: 10.1007/s11663-001-0041-7
|View full text |Cite
|
Sign up to set email alerts
|

Dephosphorization of ferromanganese using BaCO3-based fluxes by submerged injection of powders: A preliminary kinetic study

Abstract: contact reaction is rather harmful, when the transitory reac-Dephosphorization of tion is also high, because uneconomically excess species Ferromanganese using BaCO 3transport beyond the equilibrium value takes place to the Based Fluxes by Submerged slag phase, which later reverts back to the metal phase. However, an increase in permanent contact reaction, at a Injection of Powders: A Preliminarycomparatively lower rate of transitory reaction, was found Kinetic Study to be beneficial. Based on their laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 3 publications
2
18
0
Order By: Relevance
“…This can be understood with 1) the visual observation that bottom Ar blowing pushed the top slag onto the crucible wall, reducing slag/steel contact area, and 2) the aluminium would react with oxygen in Ar gas, resulting a high content of Al2O3 in slag (see in Tables 5 and 6) and consequently decreasing the sulphide capacity and sulphur distribution ratio, both of the decreasing of contact area and sulphide distribution ratio weaken the desulphurisation kinetics; (3) the desulphurisation rate decreases with decreasing the sulphur content in the steel, implying a difficulty for ultra-low sulphur steel refining; (4) with a similar mass transfer coefficient of sulphur in the slag phase, a high equilibrated sulphur distribution ratio between slag and steel could result in the fast desulphurisation rate. Furthermore, the fitted mass transfer coefficients of sulphur in slag phase are in the same order of magnitude obtained by other researchers, 3,18) suggesting a promising application of the present kinetic model. A relatively lower mass transfer coefficient is obtained in Test No.…”
Section: Calculated Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…This can be understood with 1) the visual observation that bottom Ar blowing pushed the top slag onto the crucible wall, reducing slag/steel contact area, and 2) the aluminium would react with oxygen in Ar gas, resulting a high content of Al2O3 in slag (see in Tables 5 and 6) and consequently decreasing the sulphide capacity and sulphur distribution ratio, both of the decreasing of contact area and sulphide distribution ratio weaken the desulphurisation kinetics; (3) the desulphurisation rate decreases with decreasing the sulphur content in the steel, implying a difficulty for ultra-low sulphur steel refining; (4) with a similar mass transfer coefficient of sulphur in the slag phase, a high equilibrated sulphur distribution ratio between slag and steel could result in the fast desulphurisation rate. Furthermore, the fitted mass transfer coefficients of sulphur in slag phase are in the same order of magnitude obtained by other researchers, 3,18) suggesting a promising application of the present kinetic model. A relatively lower mass transfer coefficient is obtained in Test No.…”
Section: Calculated Resultssupporting
confidence: 85%
“…However, the slag additions, in present tests, can result in the change of interface velocity and this would result in a change in the Sherwood number. Moreover, the sulphur diffusion coefficient in slag phase is a function of slag chemistry, 18) which varies with slag additions during the treatment. Therefore, the model is fit to the experimental data by obtaining the best fit values for the total mass transfer coefficients.…”
Section: Calculated Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of both the industrial and laboratory tests, it can be concluded that the present synthetic CA slag is feasible for the low sulphur stainless steel refining process. (4) the fitted mass transfer coefficients of sulphur in slag phase is 1.2 × 10 -6 m/s, which is in the same order of magnitude obtained by other researchers, 8,12,21) suggesting the reliability of the present kinetic model.…”
Section: Desulphurisation Kineticssupporting
confidence: 86%
“…The rate-limiting step is the transfer of [S] from liquid steel towards the slag-steel interface 17,24) or (S 2 − ) from the slag or injected powders towards the interface. [25][26][27][28] …”
Section: Kinetic Model Concept For Powder Injectionmentioning
confidence: 99%